Thrombophilia - Maurizio Zangari; Francesca Elice; Guido Tricot; Louis Fink (AboutScience Srl, 2008)
Thrombophilia or hypercoagulable state is a clinical condition characterized by a tendency to develop venous (less frequently arterial) thrombosis. The development of a venous thromboembolic episode (VTE) is the result of environmental risk factors such as age, male sex, obesity, the exposure to "risk periods" of immobilization, trauma, cancer, pregnancy or the use of exogenous hormones or antineoplastic medications often on a background of a congenital procoagulant state. Table 1 summarizes the most frequently inherited and acquired thrombophilic conditions in a population of patients with a first episode of VTE.In patients with venous thrombosis before the early nineties a biologic cause of thrombophilia was detectable in only 5% to 15% of cases and was confined to deficiencies of antithrombin, protein C, and protein S. The discovery of two prothrombotic mutations prevalent in white populations, the factor V-Arg506Gln mutation (factor V Leiden) and the prothrombin G20210A mutation has significantly increased the number of patients with recognizable hereditary risk factor. The antiphospholipid antibody syndrome and elevated plasma homocysteine levels are also frequently identifiable risk factors in patients presenting with venous as well as arterial thrombosis.